SUSTAINABILITY REPORTING AND SHAREHOLDERS’ INVESTMENT DECISIONS IN AFRICA - Emmanuel, Chinanu; Folorunsho, Akande; Atanda, Olabamiji; Akintoye, Ishola Rufus (International Journal of Accounting & Finance Review, 2024)
Shareholders’ investment decisions are fraught with several challenges that undermine their optimality and pose detrimental effects to firms on the long run. Sustainability reporting by firms is advanced as a mechanism that drives the efficacy of investors’ decisions.  This study investigates the effect of sustainability reporting on shareholders’ investment decisions in Africa.  Quantitative research was employed using panel data sourced from the year end reports and financial statements of the sampled firms for a period of 20 years spanning 2004-2023.  Descriptive and inferential statistics was deployed to test the collated data and multiple regression was used to estimate the model. The measures of sustainability reporting used are environmental sustainability performance disclosure, social sustainability performance disclosure and governance sustainability disclosure. Shareholders’ investment decisions was proxied by dividend payout ratio and return on equity. Management quality was adopted as a moderating variable. The findings of the study reveal that environmental sustainability performance disclosure and governance sustainability performance disclosure have insignificant positive effect on return on equity, social sustainability performance disclosure has insignificant negative effect while management quality has significant negative effect on return on equity. Environmental Performance Disclosure has insignificant positive effect on dividend payout ratio, social performance disclosure has insignificant negative effect on dividend payout ratio, and governance performance disclosure has significant positive effect while management quality has significant negative effect.  The results depict that the measures of sustainability reporting jointly have significant effect on return on equity and dividend payout ratio in models 1 & 2 respectively.   The findings demonstrate that sustainability reporting is a significant factor that enhances shareholders’ investment decisions.  JEL Classification Codes: G11, Q56, G3.